Mollusca’s Density and Distribution Pattern in Kalangan Mangrove Forest Ecosystem - Sayu Natio Tarihoran; Susi Mei; Arsanti Arsanti; Rodhi Firmansyah; Dian Fitria M; Tengku Muhammad Ghazali; Daniel Sinaga (Jurnal Moluska Indonesia, 2021)
Shellfish is one of the organisms that have habitat in mangrove forests because it has a muddy substrate. However, mangrove forests in the coastal area of Kalangan, Central Tapanuli Regency have suffered environmental damage. Therefore, a research on the density and pattern of shellfish distribution is needed to be a recommendation for optimal, sutainable mangrove forest management. This research was conducted in September 2020. The method used in determining the location of sampling is purposive sampling method using 1x1m2 plot on the surface of muddy sand substrate. The results showed that the population density of Anodentia edentula 32 ind/m2 at Point I with grouping distribution patterns; Cerithidea cingulata 74 ind/m2 at Point I (grouping), 156 ind/m2 in Point II (grouping), and 126 ind/m2 in Point III (grouping); Cerithidea quadrata 2 ind/m2 in Point I (uniform); Clypeomorus sp 12 ind/m2 at Point I (uniform); Nerites sp 178 ind/m2 at Point I (group), 94 ind/m2 at Point II (group), and 418ind/m2 at Point III (grouping); Donax trunculus 3 ind/m2 at Point I (uniform); Sulcospira testudinaria 1 ind/m2 at Point I (uniform), 79 ind/m2 at Point II (grouping), and 32 ind/m2 at Point III (random), and Telescopium telescopium 2 ind/m2 at Point I (uniform), and 1 ind/m2 at Point III (random). So it can be concluded that the biodiversity of mollusca in mangrove forest ecosystems in the coastal area of Kalangan, Central Tapanuli Regency, is of low value so that it needs to be maintained for the sake of ecosystem balance and the availability of germplasm for future generations.